Utilizing the RSA Algorithm to Enhance the Security of Real-World Applications (Informatica, 2025)
In the recent times, during COVID-19 statics tell, cyber-attacks have increased by up to 37%. While the lockdown all the companies are leveraging technologies accessible via internet to conduct their day to today work. The amount of transfer of data and information be it personal or otherwise has also escalated. Today, cyberattack is a major threat to every company. On the other hand, companies and hackers have been trying to take the advantage of it to attack people. Thus, security of data and keeping individuals or enterprises information safe has become a crucial area of research. Cryptography provides major breakthroughs by providing techniques to encrypt the data before sharing it over internet. But with increasing computational power of technology and AI; there’s a need to make advancements to these algorithms. This paper provides a novel approach to RSA algorithm to increase the security and performance. The proposed algorithm is compared with the standard RSA algorithm by varying the number of primes. An ML model is also proposed which suggests the number of primes required to encrypt the message to optimize the processing time based on the length of the message and the execution time.